Learning based on education for sustainable development as a solution to global environmental problems - Nugraheny, Devita Cahyani; Vioreza, Niken; Dwiprabowo, Risky (Nashir Al-Kutub Indonesia, 2024)
Environmental problems were still a significant global issue and challenge that was not only limited to the national or regional level. This problem was closely related to economic and social development, which was often triggered by human activities that were not environmentally friendly. In addressing this problem, the concept of sustainable development was coined with three main dimensions: economic, social, and environmental. Education played an important role in supporting sustainable development through the application of education for sustainable development in learning. This research aimed to describe the implementation of education for sustainable development-based learning in schools as a solution to global environmental problems. The method used in this research was a literature study, which included six stages: determining the topic, searching for related literature, developing arguments, conducting a survey of relevant literature, criticizing the literature, and writing a review. The research results showed that education for sustainable development-based learning in schools could be implemented using appropriate learning models and supported by various education for sustainable development-based learning resources. This implementation proved effective in increasing students' awareness and knowledge of environmental issues and encouraging more environmentally friendly actions.